Aplicación de las Normativas de Contratación Pública en el Departamento Financiero del Gobierno Autónomo Descentralizado Parroquial de Febres Cordero - Barbera Burgos, Darwin Lenin (2018)
Public procurement regulations are guides that allow the servers in charge of their application to take care of and manage the resources provided by the Ecuadorian state to public sector entities, which will be managed in an efficient manner so that any process it is evidenced in a transparent manner, facilitating any examination by the entity that regulates its proper use. The objective of this case study is to publicize the processes that are carried out in the financial department of the Parish Autonomous Decentralized Government of Febres Cordero (GADP-FC), focused on what is established in the public procurement regulations issued by the General Assembly, with the intention to safeguard all the processes that are handled in an entity that belongs directly to the state and in this way be able to make use of the resources and thus improve the communities belonging to the GADP. The Autonomous Decentralized Parochial Government has as institutional objectives; plan, build and maintain the works that are executed in it and ensure the quality of public services and have at their disposal the execution of different processes which will be applied according to the needs required by the community, making them comply in a legal and orderly manner, as determined by the Organic Law of the National System of Public Procurement (LOSNCP) and its General Regulations. The APPLICATION OF THE PUBLIC CONTRACTING STANDARDS IN THE FINANCIAL DEPARTMENT OF THE AUTONOMOUS DECENTRALIZED GOVERNMENT OF FEBRUARY CORDERO will be analyzed, applying the explanatory method under the research sub-line financial management and social commitment, the same one that was resorted to the use of two survey and interview to the personnel that works in the financial department of the entity since through this way it is possible to know the problems that this department brings; which will analyze the causes that lead to the application of public procurement rules in the processes carried out by the GADP, and in this way be able to fully comply with the objectives and competencies that it has.